Isosorbide, pyrogallol, and limonene-containing thiol-ene photocured bio-based organogels for the cleaning of artworks - (:unkn) unknown (My University, 2022)
The development of bio-based gels for the cleaning of historical artworks is an attractive area of re-search. In this work, we designed thiolene photocured organogels by combining five different thiol or allyl functionalized bio-based monomers. Isosorbide, pyrogallol, and limonene were used as the bio-based building blocks for derivatization. The chemical structures of the synthesized monomers were characterized by proton nuclear magnetic resonance spectroscopy (H-1 NMR) and Fourier transform infrared (FTIR) spectroscopy. The organogel structures were examined by FTIR analysis. Thermal and thermomechanical properties of the gels were determined by thermogravimetric analyses (TGA) and dynamic mechanical analysis (DMA), respectively. The swelling behavior of the organogels in various solvents was also investigated. Gels swelled most in dimethyl carbonate (DMC). The confinement of the solvents in the gels de-creased their evaporation rate. The organogels displayed a two-stage degradation profile and were found to be thermally stable up to & SIM;200 & DEG;C. The gels were evaluated for the cleaning of dammar-based varnish from historical artwork. DMC swollen gels were found to be effective in removing the varnish from the surface of the artwork. None of the prepared gels adhered to the surface layer of the paintings. Scanning electron microscope (SEM) images proved that the surfaces were cleaned without leaving any gel residue. (C) 2022 Elsevier Masson SAS. All rights reserved.
Keywords: Sosyal ve Beşeri Bilimler; Arkeoloji ve Sanat Tarihi; Sanat; Jeoloji Mühendisliği; Kimya; Analitik Kimya; Fizikokimya; Spektroskopi; Temel Bilimler; Mühendislik ve Teknoloji; Social Sciences and Humanities; Archaelogy and History of Art; Art; Geological Engineering; Chemistry; Analytical Chemistry; Physical Chemistry; Spectroscopy; Natural Sciences; Engineering and Technology; ARKEOLOJİ; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); SANAT; KİMYA, ANALİTİK; Temel Bilimler (SCI); YER BİLİMİ, MULTİDİSİPLİNER; Yerbilimleri; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); SPEKTROSKOPİ; JEOLOJİ; ARCHAEOLOGY; ARTS & HUMANITIES; Arts & Humanities (AHCI); ART; CHEMISTRY, ANALYTICAL; CHEMISTRY; Natural Sciences (SCI); GEOSCIENCES, MULTIDISCIPLINARY; GEOSCIENCES; MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); SPECTROSCOPY; GEOLOGY; Genel Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (çeşitli); Arkeoloji (sanat ve beşeri bilimler); Koruma; Müzecilik; Arkeoloji; Görsel Sanatlar ve Gösteri Sanatları; Metaller ve Alaşımlar; Malzeme Kimyası; Stratigrafi; Filtrasyon ve Ayırma; Kimya (çeşitli); Genel Malzeme Bilimi; Geoteknik Mühendisliği ve Mühendislik Jeolojisi; Genel Kimya; Jeoloji; Ekonomik Jeoloji; Sosyal Bilimler ve Beşeri Bilimler; Fizik Bilimleri; General Arts and Humanities; Arts and Humanities (miscellaneous); Archeology (arts and humanities); Conservation; Museology; Archeology; Visual Arts and Performing Arts; Metals and Alloys; Materials Chemistry; Stratigraphy; Filtration and Separation; Chemistry (miscellaneous); General Materials Science; Geotechnical Engineering and Engineering Geology; General Chemistry; Geology; Economic Geology; Social Sciences & Humanities; Physical Sciences; Thiol-ene photopolymerization; Painting; Cleaning; Isosorbide; Pyrogallol; Limonene; COATINGS; ACID; GEL; HYDROGELS; REMOVAL